rút gọn (3/2-((x^4-(x^4+1)/(x^2+1)).((x^3-x(4x-1)-4)/(x^7+6x^2-x-6)):(x^2+29x+78)/(3x^2+12x-36)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(\left(x+1\right)^3-\left(x-1\right)^3-6\left(x-1\right)^2=5\\ < =>x^3+3x^2+3x+1-\left(x^3-3x^2+3x-1\right)-6\left(x^2-2x+1\right)=5\\ < =>x^3+3x^2+3x+1-x^3+3x^2-3x+1-6x^2+12x-6=5\\ < =>12x-4=5\\ < =>12x=9\\ < =>x=\dfrac{9}{12}=\dfrac{3}{4}\)
(x+1)3-(x-1)3 - 6(x-1)2 = 5
x3 + 3x2 + 3x + 1 - x3 + 3x2 -3x + 1 - 6x2 + 12x -6 = 5
12x - 4 = 5
12x = 9
x = 9 : 12
x = 3/4
D = 7 - 10x + x2
D = x2 - 10x + 25 - 18
D = (x - 5)2 - 18
( x- 5 )2 ≥ 0 ⇔ (x-5)2 -18 ≥ -18⇔D(min) = -18 ⇔ x = 5
Xét : \(\sqrt{7-2\sqrt{6}}=\sqrt{6-2\sqrt{6}+1}\\ =\sqrt{\sqrt{6}^2-2.\sqrt{6}.1+1^2}\\ =\sqrt{\left(\sqrt{6}-1\right)^2}=\left|\sqrt{6}-1\right|=\sqrt{6}-1\)
( Vì : \(\sqrt{6}>1=>\sqrt{6}-1>0\) )
Ta có :
\(\dfrac{\sqrt{7-2\sqrt{6}}-2}{\sqrt{7-2\sqrt{6}}+1}=\dfrac{\sqrt{6}-1-2}{\sqrt{6}-1+1}=\dfrac{\sqrt{6}-3}{\sqrt{6}}\\ =\dfrac{\sqrt{6}\left(\sqrt{6}-3\right)}{6}=\dfrac{6-3\sqrt{6}}{6}\)
bài lớp 9 ạ:>
\(\sqrt{7-2\sqrt{6}}=\sqrt{\left(\sqrt{6}-1\right)^2}=\sqrt{6}-1\)
biểu thức trên =\(\dfrac{\sqrt{6}-3}{\sqrt{6}}=1-\dfrac{3}{\sqrt{6}}=1-\dfrac{\sqrt{6}}{2}\)